Embratel, história e cultura: efeitos da política nacional de telecomunicações no desenvolvimento socieconômico do Espírito Santo (1980-1989) - Felipe, José Mauriene Araújo (2005)
It investigates the history and organizational culture of the Brazilian Company of Telecommunications (EMBRATEL). So we analyze the impacts of national policy of telecommunications for the social and economical development of Espírito Santo State. The decade of 1980 is taken as the guidance for making this thesis because of the importance of the period which marks the finish of the military regime and the return of a slow and dramatic democracy process. As a Company of Brazilian Government, EMBRATEL was created by the military Escola Superior de Guerra – ESG, where the Doctrine of National Security, based on the Doctrine of National War College of Washington-USA, was born. It is recognized that the ESG ideology was fundamental as an instrument of orientation for installing the National System of Telecommunications (SNT) in a short time, so that the integration of the large Brazilian hinterlands was its target. Behind that target strategy there was the purpose for assuring the national security, and promoting industrialization and modernization of Brazil under the military regime domination (period: 1964-1985). This Thesis is according to the following subject matters: Chapter I – EMBRATEL and The Development Ideology of National Integration and Security; Chapter II – Organizational Culture of EMBRATEL: Study on “Embratelino” Identity Construction; Chapter III – Telecommunications in The Social and Economical Process of Integration and Modernization of Espírito Santo State (1980-1989). The data collect is based on EMBRATEL documents analysis. Eight ex-employees of the state Company were interviewed so that their testimonies were submitted to a very detailed transcription, and transformed into eight historical documents. Specific books and annual reports of EMBRATEL performance during the 1980s were taken into consideration. It is corroborated that the “embratelina” organizational culture, risen from the radical and dictatorial military discipline, was – in a way of a paradox – fundamental for its success. It made EMBRATEL becomes one of the greatest worldwide companies of telecommunications. Its performance was recognized as relevant to integrate the Espírito Santo hinterlands. The EMBRATEL modern technological equipments installation contributed to the process of socioeconomic development of Espírito Santo State, which was definitively modernized, and integrated into Brazilian and world economy.